Study of Genus Phis Homoptera Aphididae: Morphometric analysis and classification of Anuraphis species in the western Palaearctic region (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The most material morphometric characteristics of six sorts of the family Anuraphis Del Guercio were taken a gander at. Anuraphis shaposhnikovisp. nov. is depicted and its morphological differences from the immovably related species Anuraphis subterranea are presented. The new species was accumulated in Sicily and in the central space of the Italian projection on Magydaris pastinacea (Lam.) Paol. (Apiaceae) and Opopanax chironium (L.) Koch (Apiaceae), which are its helper have plants. A key to the viviparous changes (apterae and alatae) of the seven western Palaearctic species living on discretionary hosts is given. Discriminant limits have been resolved to confine both apterae and alatae of A. shaposhnikovi and A. subterranea.